2007
DOI: 10.1111/j.1745-7599.2006.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and physical fitness counseling patterns of adult nurse practitioners

Abstract: NPs can use specific physical fitness measures to help assess, guide, and/or motivate physical activity in their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 14 publications
2
39
0
2
Order By: Relevance
“…Other researches done on the same issue (Buchholz and Purath, 2007;Roos, 2014;Abramson et al, 2008) show time and knowledge being the major barriers to exercise prescription. In a review done by Seth (2014) in the United Kingdom(UK) showed that barriers to exercise prescription in the UK included scarcity of referral pathways, lack of time, not having adequate access to reference material to guide them in the practical aspects of exercise prescription and a lack of confidence in the services they are referred to.It should be considered that relative contraindications e.g.…”
Section: Effectiveness Of Primary Care Interventionsmentioning
confidence: 99%
“…Other researches done on the same issue (Buchholz and Purath, 2007;Roos, 2014;Abramson et al, 2008) show time and knowledge being the major barriers to exercise prescription. In a review done by Seth (2014) in the United Kingdom(UK) showed that barriers to exercise prescription in the UK included scarcity of referral pathways, lack of time, not having adequate access to reference material to guide them in the practical aspects of exercise prescription and a lack of confidence in the services they are referred to.It should be considered that relative contraindications e.g.…”
Section: Effectiveness Of Primary Care Interventionsmentioning
confidence: 99%
“…A second, even more important barrier is the lack of education and training health care providers have with regard to physical activity counseling and prescription (Buchholz and Purath, 2007;Douglas et al, 2006;Gornall et al, 2008;McKenna et al, 1998). It has been found that the main source of physical activity information is the mass media for 27% of current health care providers and 48% of future health care providers (Parker et al, 2009).…”
Section: Barriers To Providing Physical Activity Counselingmentioning
confidence: 99%
“…One of the main concerns cited is a lack of time (Buchholz and Purath, 2007;Harris et al, 2004;McKenna et al, 1998;Parker et al, 2009;Schmid et al, 2009). Although physicians see the primary care system and their role in primary prevention as important (Schmid et al, 2009), they do not believe that using appointments for behaviour change counseling would be appropriate (Harris et al, 2004) and they feel that their time could be better spent addressing more important concerns (Buchholz and Purath, 2007).…”
Section: Barriers To Providing Physical Activity Counselingmentioning
confidence: 99%
See 2 more Smart Citations